2016
DOI: 10.1146/annurev-neuro-061010-113708
|View full text |Cite
|
Sign up to set email alerts
|

New Perspectives on Genomic Imprinting, an Essential and Multifaceted Mode of Epigenetic Control in the Developing and Adult Brain

Abstract: Mammalian evolution entailed multiple innovations in gene regulation, including the emergence of genomic imprinting, an epigenetic regulation leading to the preferential expression of a gene from its maternal or paternal allele. Genomic imprinting is highly prevalent in the brain, yet, until recently, its central roles in neural processes have not been fully appreciated. Here, we provide a comprehensive survey of adult and developmental brain functions influenced by imprinted genes, from neural development and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
90
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(93 citation statements)
references
References 256 publications
(339 reference statements)
3
90
0
Order By: Relevance
“…Measures of white matter microstructure, such as FA, are also heritable (Kochunov et al, 2010). Next to this, genomic imprinting, which is a unique form of epigenetic regulation in mammals leading to the preferential expression of the maternal or paternal allele of certain genes with wide spread implications for the development and function of the brain, could play a role (Perez, Rubinstein, & Dulac, 2016). Further, shared environmental family factors (e.g., poverty) may also explain the association of depressive symptoms with structural connectivity.…”
Section: Explanationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Measures of white matter microstructure, such as FA, are also heritable (Kochunov et al, 2010). Next to this, genomic imprinting, which is a unique form of epigenetic regulation in mammals leading to the preferential expression of the maternal or paternal allele of certain genes with wide spread implications for the development and function of the brain, could play a role (Perez, Rubinstein, & Dulac, 2016). Further, shared environmental family factors (e.g., poverty) may also explain the association of depressive symptoms with structural connectivity.…”
Section: Explanationsmentioning
confidence: 99%
“…Further, shared environmental family factors (e.g., poverty) may also explain the association of depressive symptoms with structural connectivity. Next to this, genomic imprinting, which is a unique form of epigenetic regulation in mammals leading to the preferential expression of the maternal or paternal allele of certain genes with wide spread implications for the development and function of the brain, could play a role (Perez, Rubinstein, & Dulac, 2016). This potential explanation is likely as our results demonstrate that both maternal and paternal depressive symptoms were similarly related to childhood FA in the cingulum suggesting that a heritable vulnerability or shared environmental family factors or the combination of both (epigenetic processes) may play a role in this relation.…”
Section: Explanationsmentioning
confidence: 99%
“…Most significant interactions between genes showing parent-of-origin-dependent allele-specific expression biases and biallelic genes differentially expressed by cross are trans-chromosomal. This indicates that we are not identifying covariation among pairs that are controlled by the same regulatory element, as is often found among canonically imprinted genes that are controlled by the same cis-regulatory machinery 34,45 .…”
Section: Genes Showing Parent-of-origin Effects Form Highly Interconnmentioning
confidence: 80%
“…Changes caused by differential paternal care are presumably subserved by epigenetic changes, which are also mostly still undefined. Studies of genomic imprinting [49] and other modes of inheritance [50] have found evidence for paternal effects unrelated to behavior in both primates [51] and rodents [52]. However, changes in methylation or histone acetylation subsequent to paternal behavior have not yet been studied.…”
Section: Effects Of Parenting On Offspring In Animal Modelsmentioning
confidence: 99%